Comparison of Solids and Oxygen demand reduction in Shrimp Culture Wastewater Treatments with and without Water Hyacinth - Lee, Nyanti; G, Berundang; T.Y., Ling (4th International Conference on Natural Resources & Environmental Management and Environmental Safety & Health, 2009)
Shrimp aquaculture pond effluent is known to be high in suspended solids and nutrients. To reduce environmnetal pollution, shrimp water is channeled into sedimentation ponds for treatment before discharge. Since water hyacinth is commonly used to treat animal farm wastewater, this study aimed to compare solids and BOD5 reduction of sendimentation pond with and without water hyacinth. Fiberglass tanks were setup outdoor in triplicats at a commercial shrimp farm. The tanks were filled with fresh effluent from pond during harvesting. Water hyacinth was placed in three of the tanks (WH) and the other three tanks were without water hyacinth (WWH). The experiment was conductewd for 76 hours. Results showed that temperature were more available in WWH treatment than in WH treatment. pH in WWH treatment were mostly above 8 whereas in that in WH treatement were between 7 - 8. In WH treatment, TSS reduced from 125 to 11 mg/L. But in WWH treatment, the decrease was significantly less, that is, from 124 to 34 mg/L. For BOD5, in the WH treatment, the reduction was 70% but in WHH treatment, there was an increase of 10%. This study shows that shrimp effluent treated with water hyacinth has significantly better water quality in terms of TSS and BOD5 than that without water hyacinth.